Phytase supplementation on the availability of different minerals and their interactions in pigs - Shyama K (Department of Animal Nutrition, College of Veterinary and Animal Sciences, 2009)
Two feeding experiments were conducted using 100 weaned piglets to study the effect of dietary supplementation of calcium, phosphorus and phytase in different levels and their interactions on growth, nutrient digestibility, mineral availability and blood and bone mineral profile. In experiment one, sixty four weaned Large White Yorkshire x Desi piglets (32 castrated male and 32 female) belonging to the Centre for Pig Production and Research, Mannuthy were used as experimental animals. All animals were dewormed before the start of the experiment. The piglets were divided into eight groups as uniformly as possible with regard to age, sex and weight. Piglets of each group were allotted randomly into four pens with two piglets in each pen. Piglets in each replicate were maintained under identical management conditions throughout the experimental period of 88 days. Restricted feeding was followed throughout the experimental period and daily feed intake was recorded. Clean drinking water was provided ad libitum in all the pens throughout the experimental period. The animals were fed with standard grower ration with 18 per cent CP and 3200 kcal of ME/kg of feed up to 50 kg body weight and finisher ration with 16 per cent CP and 3200 kcal of ME /kg of feed from 50 kg body weight. Eight dietary treatments with two levels of calcium (0.6 and 1 per cent) and two levels of phosphorus (0.3 and 0.6 per cent) were used with phytase (750 units /kg) and without phytase in a 2x2x2 factorial completely randomized design. The pigs were weighed at the beginning of the experiment and later on at fortnightly intervals. Blood samples were collected at the beginning and on 85th day of the experiment and a digestibility trial was conducted at the end of the experiment to determine the digestibility of nutrients and percentage availability of minerals of the experimental diets by total collection method. The results of the first experiment indicated that the levels of Ca, P and phytase had no effect on average daily gain, feed efficiency and DM intake among pigs reared under the eight dietary treatments, while there was significant interaction between Ca x P (P<0.05) and Ca x phytase (P<0.01) on DM intake. The level of Ca and P and Ca x P x phytase interactions were significant for DM digestibility which resulted in lower DM digestibility for rations T3, T5 and T7 than that of other rations. Dietary levels of P and interaction between Ca x P (P<0.01) and Ca x phytase (P<0.05) were significant for EE digestibility. Hence rations T7 and T8 had lower (P<0.01) EE digestibility than the rest of the experimental rations. Crude fibre digestibility was affected by phytase and P x phytase interaction. Calcium availability was higher (P<0.01) in all phytase supplemented rations. Significant interactions between dietary Ca x phytase (P<0.01) and dietary P x phytase (P<0.05) were observed for Ca availability. Interactions between dietary levels of Ca x P (P<0.05) and Ca x phytase (P< 0.05) were found significant for availability of Cu and Mn respectively. Data on blood samples collected on 85th day revealed that phytase supplementation had significant effect (P< 0.01) on the plasma Ca levels of the animals fed the eight dietary treatments. The interaction between dietary Ca x P levels was also found significant (P< 0.01) for plasma Ca. Dietary levels of both Ca (P< 0.01) and P and interaction between Ca x P (P< 0.01), Ca x phytase and P x phytase (P<0.01) were found to affect plasma P significantly. In case of plasma Zn dietary Ca was having significant (P< 0.01) effect and the interactions between dietary Ca x P (P<0.01), Ca x phytase (P<0.05) and P x phytase (P<0.01) were also found significant. Dietary Ca, P and phytase levels had significant (P<0.05) effect on the plasma ALP activity. Cost of feed per kg body weight gain of pigs was lowest for ration T1. Ration T1 with low Ca, low P and without phytase gave similar growth and feed efficiency with lowest cost of production compared to the other rations and thus T1 was taken as the control ration for the second experiment. The second feeding experiment was conducted for 114 days using 36 weaned Large White Yorkshire x Desi weaned piglets (18 castrated males and 18 females) belonging to the Centre for Pig Production and Research, Mannuthy and the animals were randomly allotted to the three dietary treatments, T1- Control ration containing 0.6 per cent calcium and 0.3 per cent phosphorus, T2 -Control ration without any mineral supplements and with 750 units of phytase/kg feed and T3 - Control ration without phytase and mineral supplementation. A digestibility experiment was conducted to determine the digestibility of nutrients and availability of minerals. Blood samples were collected before the start of the experiment and on 16th week. Radiological examination of femur and mandibles of the representative animals of three groups at the end of the study were done. All the male animals were slaughtered on attaining slaughter weight of 70 kg and the data on dressing percentage, loin eye area, back fat thickness, weight of internal organs were collected. Photograph of rib bone was taken during slaughter and bone ash percentage, bone calcium and bone phosphorus were estimated. Kidney samples were examined histologically to assess pathological changes, if any, due to the experimental rations. Body weight of pigs belonging to T2 (phytase supplemented ration) was significantly higher (P<0.05) than that of T3 in fortnights 4, 6, 7, 8 and 9, while the difference between that of T1 and T2 were non significant in all the fortnights. There was no difference in feed efficiency and digestibility of nutrients among pigs reared under the three dietary treatments. The availability of Ca, P and Mn for T2 ration was higher than that of the control ration while the Mg availability was lower for T2 and T3 than that of T1. Zinc availability was lower for T3 than that of T1 ration. Dressing percentage was lower (P<0.01) for T2 and T3 than that of control and loin eye area was lower (P<0.05) for T3 than that of T1 and T2. There was no gross abnormality of femur and mandible on x-ray examination of pigs reared on three experimental rations. Histopathological examinations of kidney samples also were normal for pigs of T1 and T2 and T3. However ricketty beads were seen on ends of ribs on carcass evaluation, in pigs reared under T3. The bone ash content was also lower (P<0.01) for animals fed ration T3 than that of T1 and T2. Thus feeding ration without any mineral supplementation showed deleterious effects on growth, mineral availability and bone ash content, but supplementation of phytase improved utilization of nutrients and minerals than that of T3 during the period of 114 days of the experiment. Feed cost /kg gain of T1 pigs was higher than that of T2 (P< 0.01) and T3 (P< 0.05). But the difference in the cost of production between T2 and T3 were non significant (P>0.05). It can be concluded that phytase supplementation of rations resulted in decreased feed cost / kg gain.